Menguak Nilai Dan Makna Di Balik Praktik Penentuan Harga Sewa: Studi Fenomenologis Pada Pengusaha Kos-Kosan - Danang Prasdika; Robiatul Auliyah; Achdiar Redy Setiawan (InFestasi, 2018)
This research seeks to expose the practice of determining rental rates on businessservices room kos-kosan named Kos Putra Mulya. The purpose of this researchisto know the practices of the determination of rents that occur as well as uncoveringthe value and the meaning behind these practices. This study uses qualitative methodsastools in the process of the discovery answers and usethe knife as a phenomenology analysis approach to answer the value and its meanings.Theresults showed in the method of determining the price of rent conductedby Kos Putra Mulya was not based on the total cost of the activityof search efforts, but onlyusing the process of "estimate" in determining the costper-room.Thisis due to the presence of mutual cultural influence in its Treasuryactivities.Inaddition, there is cultural gotong royong, owners also instill asense of brotherhood in every effort suffered, so that business owners regardthe tenants is part of the family. And the last, the process of extracting the consciousnesstofind meaning in the term profit increase, i.e. the profit is definedas "rezekinya", while if the lossesmeant "bukan rezekinya".